Spread the opportunity for Jom Masuk UMP - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
KUALA LUMPUR, 12 December 2021 - Universiti Malaysia Pahang (UMP) offers opportunities for prospective students to obtain information on higher education in the Jom Masuk IPT 2021 Programme in conjunction with 100 Days of Malaysian Family Aspiration Showcase took place at the Kuala Lumpur Convention Centre (KLCC) for three days since 10 December 2021.